The macrophages in rheumatic diseases - Laria A (Dove Medical Press, 2016)
Antonella Laria, Alfredomaria Lurati , Mariagrazia Marrazza , Daniela Mazzocchi, Katia Angela Re, Magda Scarpellini Rheumatology Unit, Fornaroli Hospital, Magenta, Italy Abstract: Macrophages belong to the innate immune system giving us protection against pathogens. However it is known that they are also involved in rheumatic diseases. Activated macrophages have two different phenotypes related to different stimuli: M1 (classically activated) and M2 (alternatively activated). M1 macrophages release high levels of pro-inflammatory cytokines, reactive nitrogen and oxygen intermediates killing microorganisms and tumor cells; while M2 macrophages are involved in resolution of inflammation through phagocytosis of apoptotic neutrophils, reduced production of pro-inflammatory cytokines, and increased synthesis of mediators important in tissue remodeling, angiogenesis, and wound repair. The role of macrophages in the different rheumatic diseases is different according to their M1/M2 macrophages phenotype. Keywords: macrophage, rheumatic diseases